Effectiveness of problem-based learning for enhancing critical thinking, metacognition, and motivation in secondary school students - Soto Sandoval, José (2025)
This study evaluated the effect of a problem-based learning (PBL) intervention on the development of cognitive, metacognitive, and motivational skills in 10th-grade students in the Language subject at a subsidized private school in Chillán, Chile. A quasi-experimental design with intact groups was used: an experimental group (n = 45) participated in a six-session intervention using PBL, while a control group (n = 41) continued with traditional instruction. Validated instruments were applied to assess the three dimensions before and after the intervention. Results showed statistically significant improvements in the experimental group across all three variables, especially in critical thinking, compared to the control group. The latter only exhibited significant changes in critical thinking, but to a lesser extent. These findings highlight the potential of PBL as an effective pedagogical strategy to promote higher-order cognitive skills, foster self-regulated learning, and shift the teacher's role toward that of a facilitator and guide. It is concluded that the implementation of PBL has a positive impact on students' active and reflective learning. The study recommends expanding the use of this methodology to other educational levels, with gradual planning and sustained teacher support.